The justification of national technical regulation system and its transformation into European system - Кривошея, Сергій Олександрович; Дядюра, Константин Олександрович (Technology audit and production reserves, 2015)
The national technical regulation system to improve its efficiency in the transformation to the European system is reviewed and analyzed in the article. The requirements of the Directives of New (standardization) and Global (certification) approaches to strategy harmonization of national technical regulations are analyzed. During the study and analysis it is found that the technical regulation system in Ukraine is more complicated, inefficient and binding, it differs significantly from certification, standardization of the European system. The main barriers to full integration of Ukraine into the international economic system are also defined. Requirements of Directive 2006/42/EC, which regulates the design, construction, conformity assessment and placing on the market of machines and mechanisms are considered. The transformation of the national technical regulation system will ensure the elimination of technical barriers to trade between Ukraine and the EU by establishing a mechanism of self-regulation of a single European market, increase the competitiveness of domestic industry in the domestic and foreign markets, expand the boundaries of marketing, and also improve the quality and reduce the risk in relation to consumer usage of this product. The proposed strategy of harmonizing national technical regulation system to the European will improve the effectiveness of the system, promote the development of the national economy and enterprises, improve the competition, ensure consumer protection and eliminate unnecessary technical barriers to trade.